IMPROVING CAREER COUNSELING STUDENTS ON THE BASIS OF THE ANALYSIS OF THE CURRICULUM AREAS OF TRAINING IT-SPECIALISTS FACULTY OF INFORMATION TECHNOLOGY PSTU - Irina Fedosova; Olena Piatykop (Kherson State University, 2015)
The paper presents the results of a comparison of four bachelor degree at the Faculty of Information Technology PSTU: 6.040301 "Applied Mathematics", 6.040302 "Computer" 6.050101 "Computer Science" 6.050202 "Automation and computer-integrated technologies". The urgency of the problems caused by the increased demand for training IT-specialists and not readily apparent to those matriculant differences training areas. Revealed that the name of economic activities and qualification of future professionals elected after training areas are very close and not an objective factor in the choice of the matriculant. More informative is the object of activity. But for a more detailed comparison, we analyzed the curricula of training areas. Curriculum Bachelor contains several dozen disciplines. To compare them, it was decided to split the discipline plans of different directions into the following groups: basic science, IT-training, electronics and circuitry, design, modeling, control (management)